1961
DOI: 10.1063/1.1777049
|View full text |Cite
|
Sign up to set email alerts
|

Electron Spin Resonance in Semiconducting Rutile

Abstract: The ESR spectra of oxygen-deficient and doped rutile have been investigated at liquid helium temperatures. Niobium and tantalum are shown to give rise to the donors Nb4+ and Ta4+ rather than Ti3+. The spectrum of reduced rutile depends on the method of reduction. Reasons for this are discussed. Under certain circumstances, involving hydrogen reduction, a particularly simple spectrum is observed. This degenerates and is replaced by a single line as the temperature is raised. A similar effect is obtained by incr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
45
0

Year Published

1970
1970
2023
2023

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 143 publications
(46 citation statements)
references
References 8 publications
1
45
0
Order By: Relevance
“…It has been suggested that this position is the most stable for location of the titanium interstitial. 19,41 This is a reasonable assumption, since the environment for the titanium interstitial in this site is closer to that of Ti in bulk rutile. Different starting positions along the z axis were tested, and it was confirmed that the octahedral sites are the most stable positions for the titanium interstitials.…”
Section: A Point Defectsmentioning
confidence: 99%
“…It has been suggested that this position is the most stable for location of the titanium interstitial. 19,41 This is a reasonable assumption, since the environment for the titanium interstitial in this site is closer to that of Ti in bulk rutile. Different starting positions along the z axis were tested, and it was confirmed that the octahedral sites are the most stable positions for the titanium interstitials.…”
Section: A Point Defectsmentioning
confidence: 99%
“…Experimental confirmation came from µSR detection of the muonium counterpart of such a state (Cox et al 2001a, Shimomura et al 2002, as well as ESR and ENDOR detection for hydrogen itself (Hofmann et al 2002) 12 . So far, only in ZnO has a shallow-donor hydrogen state been identified by conventional magnetic resonance, although previously unexplained features associated with hydrogen in the ESR spectra of rutile-TiO 2 deserve further investigation in this light (Chester 1961(Chester , 2004. Considering the possibility that hydrogen might act similarly as an adventitious dopant in other oxides, the present paper (II) is devoted mainly to binary oxides that are visually transparent, i.e.…”
Section: Context and Scope Of The Articlementioning
confidence: 99%
“…The lineshape (see Fig. 4 for details) and the g-factor are typical features in the socalled A spectrum due to Ti 3+ ions 26,27 . Now we come to the question: how the Ti 3+ ions are generated after irradiation?…”
mentioning
confidence: 99%